Auditory hallucination management in patient with mental health issues - Ihsanudin, Ihsanudin; Pinilih, Sambodo Sriadi; Amin, Muhammad Khoirul (Universitas Muhammadiyah Magelang, 2024)
Hallucinations, characterized by altered perception of stimuli leading to exaggerated or abnormal responses, can pose significant risks, including violent behavior that may harm the individual, others, or the environment. Addressing hallucinations promptly is crucial, with hallucination management being a key intervention. This study aims to describe the characteristics of clients with hallucinations and assess the effectiveness of hallucination management. Utilizing a case study design and a purposive sampling technique, this study focused on individuals who had experienced sensory perception mental disorders with hallucinations for over a year. Data were collected through participatory observation, unstructured interviews, and documentation and analyzed using domain analysis. The findings demonstrate that hallucination management therapy significantly reduced the severity of hallucinations, transitioning from moderate to mild within six interventions. Hallucination management is effective in enhancing safety and comfort for individuals experiencing hallucinations, highlighting its critical role in mental health care. Keywords: Mental health nursing; auditory hallucination; innovation in community care; healthcare services; case studies